Popliteal artery pseudoaneurysm caused by non–penetrating trauma in a patient with hereditary multiple osteochondromatosis - Oscar Andrés Parada Duarte, MD; Juan Guillermo Arámbula Neira, MD; Valeria del Castillo Herazo, MD; María Fernanda Oviedo Lara, MD; Adriana Lucía López Polanco, MD; Andrés Felipe Durán Omaña, MD; Andrés Felipe Herrera Ortiz, MD (Radiology Case Reports, 2022)
Hereditary multiple osteochondromatosis is a genetic condition characterized by the appearance of numerous osteochondromas, which can cause pseudoaneurysms in rare cases. The following article describes a 15-year-old patient with a history of current massages as part of his gym routine, who arrived at the emergency department with 4 days of pain, and ecchymosis in the right popliteal region. Therefore, duplex ultrasonography and arteriography were performed, confirming the diagnosis of popliteal pseudoaneurysm, which was subsequently treated by open surgery, providing a satisfactory outcome.